Community Service : Helping Businesses Grow H. Ridwan By's Tenun Kubang through Business Strategy Development in The Digital Era Besti. - Besti Novianda; Indah Maya Sari; Ma’ruf; Endrizal Ridwan; Fery Andrianus (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
H. Ridwan By’s Kubang weaving strives to maintain its existence through digital marketing by using unique traditional motifs and the distinctiveness of Minangkabau motifs as a Minangkabau cultural heritage to local and international communities. By adopting digital technology and design, H. Ridwan By’s Kubang weaving can increase the attractiveness of Minangkabau weaving products, thus reaching a broader market. The research methodology used was observation and interviews with the owner and craftmen of H. Ridwan By’s Kubang weaving. The marketing strategy used is social media and e-commerce platforms to increase the visibility and accessibility of Minangkabau weaving products globally. To positively impact the business, expand the market, and introduce the richness of Minangkabau culture to the world.